PENGARUH EDUKASI KONTRASEPSI MELALUI KOMUNIKASI PERSUASIF DENGAN MEDIA POSTER SERTA VIDEO TERHADAP PENGETAHUAN CALON PENGANTIN DI KANTOR URUSAN AGAMA (KUA) KECAMATAN CILINCING TAHUN 2022 - Ade Muzayanah (2022)
Public knowledge about contraception is still very lacking, because lack of knowledge causes the use of contraception to be very low because people are afraid of things that can be caused such as bleeding, reducing breast milk production and others. The purpose of this research was to determine the effect of contraceptive education on the knowledge of bride and groom at the Cilincing District KUA which was held March-June 2022. This research used a quasi-experimental method with a pretest-posttest two group design. The sample was taken by purposive sampling technique with a total of 96 brides and grooms. The results of data analysis using the Wilcoxon signed ranks and Mann Whitney test showed that there was an influence of knowledge about contraception on the bride and groom before and after health education through persuasive communication methods (value p= 0.000) there were differences in the effectiveness of contraceptive education through media poster and video (value p=0.000). Contraceptive education with video media is more effective than through poster media. The KUA suggestion can provide education through videos to increase the knowledge of the bride and groom about the use of contraception. Keywords: Bride and groom, Education, Contraception, Knowledge